2020
DOI: 10.1016/j.psj.2020.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different levels of arginine and methionine in a high-lysine diet on the immune status, performance, and carcass traits of turkeys

Abstract: We postulated that the use of appropriate levels and proportions of arginine ( Arg ) and methionine ( Met ) in compound feed with high lysine content ( Lys ) would make it possible to fully exploit the growth potential of modern fattening turkey crossbreds, without compromising their immune system. The aim of this study was to determine the effect of different ratios of Arg and Met in diets with high Lys content on the performance and immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 47 publications
(71 reference statements)
1
19
0
Order By: Relevance
“…According to Yin et al 42 , dietary Lys deficiency impairs amino acid metabolism and leads to cell apoptosis, thus increasing Casp 3 levels. In one of our previous experiments, neither a decrease in Arg content from 100 to 90% Lys nor its increase to 110% Lys in high-Lys diets 2 affected Casp 3 or Casp 8 levels in turkeys 17 . In another study of turkeys fed low-Lys diets 1 , an increase in Arg content to 110% Lys increased Casp 3 levels 14 .…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…According to Yin et al 42 , dietary Lys deficiency impairs amino acid metabolism and leads to cell apoptosis, thus increasing Casp 3 levels. In one of our previous experiments, neither a decrease in Arg content from 100 to 90% Lys nor its increase to 110% Lys in high-Lys diets 2 affected Casp 3 or Casp 8 levels in turkeys 17 . In another study of turkeys fed low-Lys diets 1 , an increase in Arg content to 110% Lys increased Casp 3 levels 14 .…”
Section: Discussionmentioning
confidence: 64%
“…Our previous findings indicate that different dietary proportions of Arg relative to Lys (90%, 100% and 110% Lys) in diets with high Lys content, close to the recommendations of breeding companies 2 , have no influence on the growth rate of turkeys 14 . In another experiment, different concentrations of Arg (90%, 100% and 110% Lys) in low-Lys diets 1 had no effect on the final BW of turkeys, except in the youngest birds (aged 1-8 weeks) where the lowest Arg level (90% Lys) decreased BW 17 . In the present study, where turkeys received diets with Lys content consistent with NRC recommendations 1 or 10% higher, the dietary proportions of Arg relative to Lys (95% and 105% Lys) had no influence on the FCR or final BW.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…It was found that diets with increased levels of Met (45% relative to the content of dietary Lys) and Arg (110% relative to the content of dietary Lys), as compared with the nutrient requirements of turkeys (NRC recommendations) [ 9 ], led to an increase in plasma albumin concentration and in the blood concentrations of caspase-3 and caspase-8. In another study [ 13 ], different dietary Arg:Met ratios affected the performance and immune status of growing turkeys. A higher Arg level in the diet (110% vs. 90% relative to Lys content, close to the BUT recommendations [ 8 ]) decreased the blood concentrations of proinflammatory cytokines (including tumor necrosis factor alpha and interleukin 6), and immunoglobulin Y.…”
Section: Introductionmentioning
confidence: 99%